Realizing the Rights of Eldery: Social Services for the Elderly Community In Banyumas Central Java - Ageng Widodo; Imam Alfi; Asyabudin (Journal of Religion and Social Transformation, 2024)
This study aims to gather information, implement, and explore social services for the elderly in Banyumas Regency, with a particular focus on the application of the principles of social programs for the elderly as outlined by the United Nations (UN). Social services, as an integral part of social policy, are implemented to achieve a key social objective: addressing social problems and fulfilling social needs. Consequently, the research seeks to answer the primary question is how are social services for the elderly implemented in Banyumas Regency. The research adopts a descriptive qualitative method to examine social phenomena related to the elderly. This approach produces descriptive data in written form based on insights from informants, including companions, social workers, and the elderly themselves. The findings reveal that the implementation of social services for the elderly in Banyumas Regency adheres to the five UN principles: independence, participation, care, self-fulfillment, and dignity. These principles serve as a framework for ensuring comprehensive and effective support for the elderly population. The research concludes that social services for the elderly in Banyumas Regency effectively align with the five UN principles.